The Correlation between Sleep Quality and Blood Glucose Levels in Patients with Type 2 Diabetes at Dr. Chasan Boesoirie Regional Public Hospital, Ternate, North Maluku - Umar, Mariam; Kurniawan, Andi Surya; Dafir Firdaus, Achmad (Jurnal Ilmiah Kesehatan, 2025)
Diabetes is characterized by hyperglycemia due to insulin deficiency or resistance, causing chronic complications in various organs. Poor sleep quality can worsen insulin resistance and increase the risk of complications of diabetes. This study analyzes the correlation between sleep quality and blood glucose levels in patients with type 2 diabetes at Dr. Chasan Boesoirie Regional Public Hospital, North Maluku. This study used a cross-sectional design. It was conducted from June 2024 to July 2024 at Dr. Chasan Boesoirie Regional Public Hospital. The population was 800 patients with type 2 diabetes at Dr. Chasan Boesoirie Ternate Hospital. There were 89 respondents by consecutive sampling. The instruments used the Pittsburgh Sleep Quality Index (PSQI) for sleep quality and GlucoDr for blood glucose levels. Data analysis used the Chi-Square test with a significance level of 0.05. The results showed that most respondents had moderate sleep quality, with 54 respondents (60.7%). In addition, most respondents have blood glucose levels in the poor category, with blood sugar levels >160 mg/dL, as many as 59 respondents (66.3%). The Chi-Square statistical test analysis showed a p=0.011 (p<0.05). Thus, there was a correlation between sleep quality and blood glucose levels in type 2 diabetes patients. In conclusion, sleep quality correlates with blood glucose levels in patients with type 2 diabetes at Dr. Chasan Boesoirie Regional Public Hospital, North Maluku. Further research should explore other factors affecting blood glucose control in people with type 2 diabetes.